2020
DOI: 10.1126/scitranslmed.abd5487
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to SARS-CoV-2 infection in hospitalized pediatric and adult patients

Abstract: Children and youth infected with SARS-CoV-2 have milder disease than do adults and, even among those with the recently described multi-system inflammatory syndrome (MIS-C), mortality is rare. The reasons for the differences in clinical manifestations are unknown, but suggest that age-dependent factors may modulate the anti-viral immune response. We compared cytokine, humoral, and cellular immune responses in pediatric (children and youth, age < 24 years) (n=65) and adult (n=60) patients with COVID-19 at a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
381
8
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(447 citation statements)
references
References 24 publications
30
381
8
6
Order By: Relevance
“…Interestingly, females seem to mount a somewhat stronger T cell activation following SARS-CoV-2 infection (13) and disruption of T and B cell coordination has been implicated in elderly patients with severe COVID-19 (14). On the other end of the age spectrum, decreased frequencies of IFNγ + CD4 + and CD25 + CD4 + T cells have been described in hospitalized pediatric patients, who have shorter lengths of stay compared with their adult counterparts (15). In conjunction with age and sex, host and viral factors probably also play a role in the early immune defense and coordination of the early SARS-CoV-2-specific T cell response.…”
Section: T Cells In Acute Sars-cov-2 Infectionmentioning
confidence: 99%
“…Interestingly, females seem to mount a somewhat stronger T cell activation following SARS-CoV-2 infection (13) and disruption of T and B cell coordination has been implicated in elderly patients with severe COVID-19 (14). On the other end of the age spectrum, decreased frequencies of IFNγ + CD4 + and CD25 + CD4 + T cells have been described in hospitalized pediatric patients, who have shorter lengths of stay compared with their adult counterparts (15). In conjunction with age and sex, host and viral factors probably also play a role in the early immune defense and coordination of the early SARS-CoV-2-specific T cell response.…”
Section: T Cells In Acute Sars-cov-2 Infectionmentioning
confidence: 99%
“…Children are thought to be less susceptible than adults to SARS-CoV-2 (9), and COVID-19 has been documented much and (e) absence of chronic comorbidities that compromise the integrity of the vascular endothelium (13).…”
Section: A Sars-cov-2-associated Hyperinflammatory Syndrome In Childrenmentioning
confidence: 99%
“…While the specific mechanism or mechanisms that protect children from severe COVID-19 are unclear (13), there are five leading theories. Compared with older adults, younger individuals may have (a) a more robust innate immune response during early infection that allows for early control of viral replication; (b) a less robust matory syndrome, children and adults with MIS-C/A present more often with gastrointestinal symptoms and less often with respiratory symptoms and thrombotic sequelae.…”
Section: A Sars-cov-2-associated Hyperinflammatory Syndrome In Childrenmentioning
confidence: 99%
“…Moreover, some individuals with mild SARS-CoV-2 infection develop T cell responses in the absence of antibody seroconversion (45). In addition, a recent study examining immune responses in pediatric compared with adult patients with COVID-19 infection (and for pediatrics, acute COVID-19 and MIS-C patients were included) found that adults with COVID-19 were more likely to have neutralizing antibody titers compared with children, as well as lower IL-17A and interferon gamma responses, and children in this study did not have differences in anti-spike antibody titers when compared to adults (63). Of note, some of these studies so far have relatively small numbers and larger studies to clarify the immune response profile distinctions amongst children with acute COVID-19 compared with MIS-C compared with adults with acute COVID-19 (severe and less severe/asymptomatic) are needed, especially in the context of the COVID-19 vaccine development efforts.…”
Section: Coinfections With Respiratory Virusesmentioning
confidence: 70%